Factors associated with preferred type of delivery among pregnant women in Elazig City, Turkey - Akkus, Ibrahim Halil; Aksakal, Berrak Yildirim; Pirincci, Edibe (SEAMEO TROPMED Network, 2017)
The aim of this study was to identify factors associated with preferred type of delivery among pregnant women in Elazig City, Turkey. It is important that pregnant women be adequately informed by health professionals and guided to select the childbirth method that will best ensure their health and that of their babies. Each participant was interviewed in a face-to-face interview and a questionnaire was followed by the researcher. The questionnaire asked about previous delivery history and the factors influencing the type of delivery. The participants were also asked about their preferred method of delivery and the reasons why they answered the way they did. Participants were randomly selected from 173 family medicine centers. Inclusive criteria were pregnant women in any trimester who were registered at the family medicine center and were willing to participate in the study. A total of 628 respondents participated in the study. The mean (SD) age of participants was 28.8 (±5.4) (range: 17-45) years. Fifty-five point six percent had a primary school education and 55.9% had a husband with a high school or higher education level. Eighty-two point two percent of respondents stated they preferred vaginal birth and 17.8% preferred a cesarean birth. The higher the education and income levels the greater to preference was for cesarean birth (p<0.05).The primary reason given for preferring vaginal birth among respondents was the belief it was healthier, followed by the belief they would go home from hospital more quickly. The primary reason given by respondents for preferring a cesarean section was fear of vaginal birth, followed by the desire to avoid pain and to reduce the risk to the baby. In our study the great majority of respondents preferred vaginal delivery. However, it is clear from the interviews there is need to better educate pregnant women about the risks and benefits of each type of delivery. Further studies are needed to determine the best effective methods to provide this education. © 2017, SEAMEO TROPMED Network. All rights reserved.
Keywords: Cesarean birth; Pregnant; Vaginal birth